226k views
2 votes
Multiply. −3/7xy(−35x^3y^2)

This is REALLY IMPORTANT I NEED IT DONE BY 2/4/2018 1:00
THANK YOU (SHOW YOUR WORK OR NO POINTS)

2 Answers

6 votes
-3/7xy(-35x^3y^2)

-3/7 * -35 = 105/7 = 15
x * x^3 = x^4
y * y^2 = y^3

so u r left with : 15x^4y^3 <==
User Randomwalker
by
5.8k points
3 votes

Here the multiplication of the expression given,


-(3)/(7)xy(-35x^3y^2)

To multiply the expression first we have to multiply the signs negative and negative. We know that negative times negative will give positive.


(-)(-)(3)/(7)xy(35x^3y^2) =
+(3)/(7)xy(35x^3y^2)

Now we will multiply the numbers
(3)/(7) and 35.


((3)/(7) )(35) xy(x^3y^2)

=
((3)(35))/(7)xy(x^3y^2)

=
(105)/(7) xy(x^3y^2)

=
15xy(x^3y^2)

Now we will multiply x with x and y with y. We will use properties of exponent. We know that when base is same, we have to add the exponents only. If we have
(x^m)(x^n) = x^((m+n)).

So here x means
x^1.

Multiplying we will get here,


15xy(x^3y^2) = 15x^1y^1(x^3y^2)

=
15x^((1+3))y^((1+2))

=
15x^4y^3

We have got the required answer here.

User Awefsome
by
5.6k points